A place for vitamin supplementation and functional food in bariatric surgery?. Issue 6 (November 2019) - Aron-Wisnewsky, Judith; Clément, Karine
Abstract : Purpose of review: This article summarizes recent literature concerning vitamin deficiency and required supplementation post-bariatric surgery, focusing on vitamin D (and associated clinical adverse effect on bone loss) and on the potential implication of the gut microbiota. Recent findings: Bariatric surgery induces weight loss and metabolic improvements yet with major inter-individual variability. If it is efficient in most patients, some display poor response (i.e. patients with the lowest weight loss at 1 year or weight regain afterwards, or patients without metabolic disease remission). Despite systematic vitamin supplementation, some patients develop vitamin deficiencies leading to poor clinical outcomes, among which vitamin D deficiency associated with observed bone mass loss and fractures. Recent mechanistic studies led to understand better the involved physiopathology. Furthermore, different intervention studies tested on top of bariatric surgery (using vitamin, diet, or nutrients acting as functional food) have evaluated whether nutritional adverse outcomes could be improved. Importantly, gut microbiota involved in food digestion and metabolization and vitamin synthesis is largely perturbed during severe obesity and is partially restored post-surgery, yet again with large interindividual variability. Whether differential gut microbiota modification could be associated with vitamin deficiencies is an open question. Summary: Future clinical research studies will need to evaluate whether add-on intervention to bariatric surgery using vitamin, diet, or specific food items could help prevent nutritional deficiencies and improve clinical response observed post-surgery. Importantly, personalizing the add-on intervention post-surgery upon gut microbiota composition should be tested in predicted poor-responders to surgery as already performed during diet intervention to further improve metabolic health.